Thermophysical properties of mango pulp (Mangifera indica L. cv. Tommy Atkins) - Bon, J.; Vaquiro, H.; Benedito, J.; Telis-Romero, J. [UNESP] (Elsevier B.V., 2010)
The density, heat capacity and thermal conductivity of mango pulp (Mangifera indica L. cv. Tommy Atkins) were determined at moisture contents of between 0.9 and 0.52 kg kg(-1) (w.b.) and temperatures of between 20 and 80 degrees C. The experimental data were satisfactorily fitted (explained variation values >99.1%) as functions of the moisture content and temperature by using multivariate linear models. In the range of conditions considered, the moisture content exhibits a greater influence on the studied properties than temperature. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Thermophysical properties; Density; Thermal conductivity; Heat capacity